Influence of Plasminogen Deficiency on the Contribution of Polymorphonuclear Leucocytes to Fibrin/ogenolysis - Zeng, Biao; Bruce, David; Kril, Jillian; Ploplis, Victoria; Freedman, Ben; Brieger, David (Thrombosis and Haemostasis, 2002)
Plasminogen knock-out (PG−/−) mice provide an unique opportunity for the study of alternative mediators of fibrinolysis. Polymorphonuclear leucocytes (PMNs) contain non-plasmin fibrinolytic proteases, however the degree to which these cells contribute to fibrin(ogen) degradation in these animals is not known. Thrombi were generated in carotid arteries and jugular veins of PG−/− and wild type (PG+/+) mice following adventitial application of a 20% ferric chloride solution. PMNs, identified histologically on H&E staining and by immunohistochemistry using anti-mouse PMN RB6-8C5 antibody, accumulated within the thrombus by 6 h after the injury and peaked at 24 h. There was significantly greater retention of PMNs within the thrombi of PG−/− mice from 48 to 72 h than in the PG+/+ controls (at 72 h: PG−/− 255 ± 41 cell/mm2 (n = 5), PG+/+ 61 ± 10 cell/mm2 (n = 5), p <0.01 in the arterial thrombi; PG−/− 252 ± 50 cell/mm2 (n = 5), PG+/+ 100 ± 36 cell/mm2 (n = 5), p <0.05 in the venous thrombi), providing potential for more PMN derived fibrinolytic enzymes to be present at late times after a thrombotic challenge in PG−/− mice relative to the PG+/+ controls.Intact PMNs were elicited from the peritoneal cavities of PG−/− and PG+/+ mice following 4% thioglycolate stimulation. In vitro studies showed PMNs from PG−/− mice to release greater quantities of 10% trichloroacetic acid (TCA)-soluble fibrinopeptides from I125-labeled fibrinogen, than cells from PG+/+ controls although these differences did not become apparent until after 24 h of incubation (at 72 h incubation: PG−/− 918 n /10 X 106 cells/0.5 ml, PG+/+ 589 ng/10 X 106 cells/ ml p = 0.005). Furthermore, autoradiographic analysis of the I125labeled fibrinogen degradation products showed the cleavage pattern by PG−/− PMNs to be distinct from that produced by PG+/+ PMNs.These data suggest that a relatively greater role for PMNs-initiated fibrinolysis exists in the setting of plasminogen deficiency, although this prominence only becomes evident more than 24 h after the thrombotic insult. In addition, mechanisms responsible for the process in PG−/− mice may be distinct from those primarily responsible for the process in PMNs from PG+/+ mice.
Keywords: Fibrinolysis; plasminogen deficiency; polymorphonuclear leucocytes